Avaliação do acometimento ungueal de pacientes adultos com psoríase vulgar - Schons, Karen Regina Rosso (2013)
Psoriasis is a chronic disease that presents in individuals of all ages, affecting skin, nails and joints. Nail changes are estimated to be present in 10-80% of psoriatic patients at some point in their lives, with consequent aesthetic and functional repercussions and quality of life impairment. In Brazil, there are only a few epidemiological studies on nail psoriasis (NP) so far. The aim of this study is to evaluate the nails of a sample of psoriatic patients from the south of Brazil, determining the prevalence of nail involvement, its main characteristics and clinical associations. This is a cross-sectional study that evaluated 65 outpatients with plaque-type psoriasis treated at the Hospital Universitário de Santa Maria - RS, from January 2012 to March 2013. Skin severity was evaluated using the PASI method and the nail changes were assessed using the NAPSI score. Psoriatic arthritis was determined by CASPAR criteria. Demographic variables were assessed by specific questionnaire. The prevalence of NP was 46.1%. Patients with NP had an average of 8.1±5 nails affected and the main morfological sign found was onycholysis (80%). Most patients (63.3%) reported functional or aesthetic discomfort related to nails involvement. When compared to patients without nail changes, patients with NP showed lower mean age of onset of psoriasis (27,6±14,9 vs. 42,7±15,9 years, p=0.001) and longer duration of the disease (17,5±10,7 vs. 9,1±9,7 years, p=0.003). Patients with NP also had higher PASI score (11,1±8,3 vs. 6,5±6,1, p=0.024), higher frequency of family history of psoriasis (40% vs. 7,4%, p=0.011) and higher frequency of psoriatic arthritis (43,3 vs. 3,7, p=0,002). The NP is still poorly studied, despite its clinical consequences such as pain, functional limitation and aesthetic disorders. Its importance as a predictor of joint involvement and more severe cutaneous disease was demonstrated by this study. Family history and early onset of disease were also associated with NP.